Association of Pulse Oximetry Screening to Detection of Critical Congenital Heart Disease - Lina S; Stephany A; I.W.B Suryawan (Politeknik Kesehatan Kemenkes Bandung, 2025)
Introduction: Critical Congenital Heart Disease (CCHD) is a leading cause of infant mortality, often presenting with subtle or absent clinical signs in the newborn period. Early detection is crucial for timely intervention and improved outcomes. Pulse oximetry has emerged as a potential screening tool, but its diagnostic performance, optimal implementation protocol, and cost-effectiveness, especially compared to existing methods like physical examination and prenatal ultrasound, require comprehensive evaluation (Ewer, 2013; Thangaratinam et al., 2012). Methods: This systematic review adhered to the PRISMA 2020 guidelines. We identified 68 studies (2002-2025) including systematic reviews, meta-analyses, and primary studies (prospective/retrospective cohorts, RCTs). Eligibility criteria focused on newborns (0-28 days), pulse oximetry as a screening tool for CCHD, and reporting of diagnostic accuracy measures. Data extraction covered CCHD definitions, screening protocols, diagnostic performance, population characteristics, and comparison with other screening methods. Results: The pooled sensitivity of pulse oximetry for CCHD detection varied widely (47%-92%), while specificity was consistently high (93%-99.9%). The sensitivity variation was attributed to differences in CCHD definitions, screening timing (higher sensitivity but more false positives if done before 24 hours), and protocol details. Physical examination alone showed lower sensitivity (32%-69%). Combining pulse oximetry with physical examination significantly improved sensitivity to 92%-93%. Pulse oximetry was found to be cost-effective, with an incremental cost per timely diagnosis substantially lower than universal screening echocardiography. Implementation success depended on standardized protocols, staff education, and decision support tools (van Vliet et al., 2023; Aranguren Bello et al., 2019; Knowles et al., 2005; Londoño et al., 2017; Hom et al., 2019). Discussion: Pulse oximetry is a valuable, specific, and moderately sensitive tool for CCHD screening. Its greatest utility is realized when used in combination with physical examination, applied after 24 hours of birth to balance sensitivity and specificity, and adapted for specific populations (e.g., adjusting thresholds for altitude). It is particularly beneficial in settings with low prenatal detection rates and limited resources. However, it cannot detect all CCHD cases, especially non-cyanotic lesions like isolated coarctation of the aorta. Conclusion: The evidence strongly supports the integration of pulse oximetry into universal newborn screening programs as a cost-effective adjunct to physical examination. Future efforts should focus on standardizing CCHD definitions, optimizing context-specific protocols, and improving implementation fidelity in diverse healthcare settings, particularly in low- and middle-income countries.